Effect of Comorbid Diseases on Hospitalization and In-Hospital Mortality of Elderly Patients Who Reapplied to the Emergency Department Within 72 Hours - Uslu, Muhammed Fuad; Yilmaz, Mustafa; Atescelik, Metin; Atilgan, Feti A. (Springernature, 2023)
Objective: This study aimed to determine the effects of comorbidities on hospitalization and in-hospital mortality in patients aged 65 years and older who returned to the emergency department within 24, 48, and 72 hours of an initial visit.Methods: This study was conducted at the Department of Emergency Medicine, Firat University Faculty of Medicine, El & acirc;z & imath;& gbreve;, Turkey. It has a retrospective design and received local ethics committee approval from the university. Patients aged 65 years and older who presented to the emergency department within a one-year period (2022) were examined to identify those who returned to the emergency department within 24, 48, and 72 hours of an initial visit.Results: A total of 763 (3.2%) patients >65 years of age returned to the emergency department within the first three days of their initial visit. Of these returning patients, 349 returned within 24 hours (Group 1), 227 within 48 hours (Group 2), and 187 within 72 hours (Group 3). Being female, polypharmacy, the presence of at least one comorbidity, cancer, and chronic renal failure were found to be independent predictors of hospitalization, whereas polypharmacy was found to be an independent predictor of in-hospital mortality.Conclusion: Patients returning to the emergency department shortly after an initial visit should be assessed more diligently due to the risk of mortality.
Keywords: unplanned revisit; revisit; multimorbidity; emergency medical service; elderly people